What intrinsic factors influence responsiveness to acupuncture in pain?: a review of pre-clinical studies that used responder analysis - Yu-Kang Kim; Ji-Yeun Park; Seung-Nam Kim; Mijung Yeom; Seungmin Lee; Ju-Young Oh; Hyangsook Lee; Younbyoung Chae; Dae-Hyun Hahm; Hi-Joon Park (BMC, 2017)
Abstract Background Not many studies have investigated individual sensitivity to acupuncture. To explore the intrinsic factors related to individual responses to acupuncture, we reviewed published pre-clinical studies using responder analysis on pain. Methods We searched the PubMed and EMBASE databases to June 2015. We included pre-clinical reports describing responders and non-responders to anti-nociceptive and analgesic effects of acupuncture in animal study. We identified the potential intrinsic factors which might be related with the response to acupuncture. Results Totally, 216 potentially relevant articles were retrieved and 14 studies met our inclusion criteria. Rat (n = 1348) and rabbit (n = 56) were used, and only electroacupuncture (EA) was applied as an intervention. Results showed that high levels of cholecystokinin-8 and receptors were associated with poor responsiveness to EA. Endogenous opioids including β-endorphin and met-enkephalin, descending inhibitory norepinephrine and serotonin system, and hypothalamic 5'-AMP-activated protein kinase seemed to be associated with high-level responses. Spinal levels of neurotransmitters and pro-inflammatory cytokines were also differentially expressed depending on the EA sensitiveness. In the central nervous system, hypothalamus, periaqueductal grey, pituitary gland, and spinal cord were suggested to be involved in the EA responsiveness. Identified individual variations did not seem to be accidental, as the responsiveness to EA was replicated over time. However, methodological issues such as reproducibility, cut-off criteria, and clinical relevance need to be further elaborated. Conclusion Our study suggests that the identification of the biological factors differentiating responders from non-responders is necessary and it may aid in understanding how acupuncture modulates pain.